2018
DOI: 10.1002/mnfr.201700890
|View full text |Cite|
|
Sign up to set email alerts
|

Epigallocatechin Gallate Reduces Amyloid β‐Induced Neurotoxicity via Inhibiting Endoplasmic Reticulum Stress‐Mediated Apoptosis

Abstract: These results indicate that EGCG attenuates the neurotoxicity in Alzheimer's disease (AD) via a novel mechanism that involves inhibition of ER-stress-associated neuronal apoptosis in vitro and in vivo, suggesting the tremendous potential of EGCG for use in a nutritional preventive strategy against AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 44 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…In vitro SH-SY5Y cells/human Aβ [80] In vivo APP/PS1 mouse model of AD Tunicamycin or Tapsigargin [80] Taxifolin…”
Section: Epigallocatechinmentioning
confidence: 99%
“…In vitro SH-SY5Y cells/human Aβ [80] In vivo APP/PS1 mouse model of AD Tunicamycin or Tapsigargin [80] Taxifolin…”
Section: Epigallocatechinmentioning
confidence: 99%
“…EGCG, phyllanthin and hypophyllanthin have been known for their capability in protecting cellular and tissue damages from reactive oxygen species and ER stress in various cell cultures and animal models. [ 11,12,14,15,27 ] In our previous study, we demonstrated that these three polyphenolic antioxidants unexpectedly elicited different effects on indomethacin‐ and diclofenac‐induced cytotoxicity in Caco‐2 cells. [ 1 ] EGCG prevented NSAID‐induced Caco‐2 apoptosis via inhibition of CHOP‐related ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…These three polyphenols have been associated with various health‐promoting effects such as antioxidant, anti‐inflammatory, anti‐microbial and cytoprotective activities. [ 10–15 ] Their cytoprotective effect may involve multi‐mechanisms, particularly reduction of cellular stresses and oxidative damages. However, cytoprotective potential and mechanisms of these antioxidants against NSAID‐induced enteropathy have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously EGCG inhibited neuronal apoptosis with reducing ER abnormal ultrastructural swelling and downregulating ERS-associated proteins in APP/PS1 transgenic mice. In conclusion, EGCG decreased the neurotoxicity via decreasing ERS related apoptosis in the AD [ 103 , 104 ]. In transient focal cerebral ischemia rat models, EGCG treatment after ischemia inhibited ERS with decreasing the expression of glucose-regulated caspase-12, CHOP, and GRP78, and improved the neurological status via inhibiting TRPC6 proteolysis and activating CREB in the MEK/ERK pathway [ 105 ].…”
Section: The Role Of Egcg In Ers-induced Apoptosis and Human Diseasesmentioning
confidence: 99%